The Hepato-Renal Chemistries of Rats Fed with Pentaclethra Macrophylla (Oil Bean Seed) - Agoro, Eni-yimini; Osioma, Ejovi; Alabrah, Peter Waibode (Khalij-Libya Journal of Dental and Medical Research, 2024)
This study was designed to examine the phytochemical composition of Pentaclethra macrophylla and its consumption effect on hepato-renal chemistries. The fermented seeds of Pentaclethra macrophylla were pulverized into fine powder and a portion of it was extracted with water to get the aqueous extract. The phytochemical constituents of fermented P. macrophylla were determined using the method of Harborne. In a similar vein, the hepato-renal biochemical parameters were determined using WHO-approved methods. The study was categorized into acute and chronic exposures. The acute involves a one-time dose of up to 5000 mg/kg of the extract orally administered to male and female rats, whereas 250, 500, 750, and 1000mg/kg of the P. macrophylla extract were orally administered daily for 90 days in chronic toxicity investigation. Bioactive compounds such as alkaloids, flavonoids, tannins, and saponins were identified in the extract. In the acute toxicity test, no death or sign of toxicity was identified. In a similar vein chronic study revealed a significant decrease (p<0.05) in concentrations of AST, ALT, and, total protein. Sodium, bicarbonate, and ALP were observed to be elevated upon administration with the maximum concentrations of the extract, whereas other parameters were not significant. The comparison of the studied parameters based on gender differences amongst the groups showed no statistically significant difference. The results have demonstrated that the extract of fermented P. macrophylla does not hurt hepato-renal biochemical parameters at the optimal concentrations, but could be deleterious at the maximum concentration as enunciated.